1994
DOI: 10.1007/bf01519984
|View full text |Cite
|
Sign up to set email alerts
|

Anti-(glioma surface antigen) monoclonal antibody G-22 recognizes overexpressed CD44 in glioma cells

Abstract: We raised an anti-glioma monoclonal antibody, named G-22, that specifically recognizes a human glioma-associated surface antigen. Proven to be useful for target imaging of malignant gliomas after radioisotope labeling and cerebrospinal fluid diagnosis by enzyme-linked immunospecific assay, G-22 was found to immunoprecipitate an 85-kDa glycoprotein of the human glioma U-251MG cell. We purified this antigen by G-22-coupled cyanogenbromide-activated Sepharose affinity chromatography, and sequence analysis demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many monoclonal antibodies against gliomas, prepared by immunizing mice with glioma cells, have been reported. Some of those antibodies have been analysed with regard to their target molecules (Schold et al, 1993;Okada et al, 1994;Romejin et al, 1994). Mouse MAbs against gliomas have also been applied in experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Many monoclonal antibodies against gliomas, prepared by immunizing mice with glioma cells, have been reported. Some of those antibodies have been analysed with regard to their target molecules (Schold et al, 1993;Okada et al, 1994;Romejin et al, 1994). Mouse MAbs against gliomas have also been applied in experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of total 54 amino-acid-residues was identical to the portion 55-108 of human CD44. We concluded that the smallest spliced form (85 kDa) of CD44 is strongly expressed in glioma cells (Okada et al, 1994).…”
mentioning
confidence: 99%
“…Several studies have found CD44 to be linked with cell-cell adhesion, cell adhesion to ECM, cell migration, as well as cancer development and metastasis [12,[57][58][59]. Nevertheless, excessive quantities of CD44s secretion have been observed in primary human gliomas as well as human glioma cell lines [4,[60][61][62]. Studies have demonstrated that, CD44 is secreted by astrocytes, mesenchymal cells, epithelial cells, as well as Schwann cells [63][64][65].…”
Section: Hyaluronic Acid Receptors and Gliomamentioning
confidence: 99%